Formation and coalescence of nanobubbles under controlled gas concentration and species - Chenliang Li; A-Man Zhang; Shiping Wang; Pu Cui (AIP Advances, 2018)
Using molecular dynamics simulations, the effects of gas concentration and species on the coalescence and growth of nanobubbles were systematically investigated. With increasing gas concentration, not only surface nanobubbles but also bulk nanobubbles are formed. The bulk nanobubble in water is less explored so far. Here, its coalescence, stability, movement trajectory and velocity are discussed. A comparison of the motion and coalescence of the bulk nanobubble to the surface nanobubble, directly demonstrates that the three-phase contact line plays a crucial role for surface nanobubble stability. Compared with the bubble size, the distance between surface nanobubbles is a more important factor to decide the merging order among three nanobubbles. The study also shows that three factors including the oversaturated gas concentration, the distance between surface nanobubbles, and the stronger solid-gas interactions influence the formation of the gas-enrichment layer at the solid-liquid interface. The result has an important significance to enhancing the boundary slip due to the presence of nanobubbles.